Case series of traumatic neglected Extensor Hallucis Longus lacerations: choice of surgical treatment based on injury type - Grassi, Miriam; Faugno, Luca; Larghi, Marco Mattia; Salvadori del Prato, Giuliano; Manzotti, Alfonso (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: Extensor Hallucis Longus (EHL) tendon rupture is a rare injury of the foot, representing only 1% of overall tendon rupture. Early diagnosis and surgical repair are recommended but there is still no consensus regarding the ideal treatment. The purpose of this study was to evaluate a case series of patients with neglected extensor hallucis longus (EHL) tendon rupture.Methods: We report a case series of 3 patients affected by traumatic neglected EHL lacerations treated with reconstructive surgery using tissue scaffolds, between November 2019 and May 2020. Demographics data, mechanism of injury, zone of injury, tendon gap, time to surgery, type of surgical repair, preoperative and postoperative functional score were collected with a minimum follow-up of 8 months.Results: The zone of injury (according to Al-Qattan classification) involved was in 1 case zone 2, in 1 case zone 4 and in the last case zone 5. The mean value of intraoperative tendon gap was of 3,4 cm. The elapsed time from injury to surgery was an average of 3,3 months. One tendon transfer surgery and two primary repairs with Krakow fashion were performed, all augmented with tissue scaffolds. The mean preoperative and postoperative American Orthopedic Foot and Ankle Society (AOFAS) scores were, respectively, 43 and 97.Conclusions: Our results highlight good functional result and satisfaction with active extension of the hallux restored in all patients. According to our experience, we recommend choosing reconstruction technique basing on the topographic zone of lesion and intraoperative tendon gap.